An Epidemiological Study of Laboratory Confirmed COVID-19 Cases Admitted in Dhaka Medical College Hospital - Hossain, Mohammad Murad; Mark, Sayeef Hossain Khan; Kabir, AKM Humayon; Das, Partha Pratim; Islam, Md Khairul; Das, Aparna (Journal of Medicine, 2020)
Background: The objective of the study was to report the epidemiological characteristics of symptomatic laboratory confirmed COVID-19 patients seeking care from Dhaka Medical College Hospital (DMCH). Methods: This observational study was conducted in department of Medicine, DMCH for the period of 2 months following ethical approval. Total 100 RT-PCR confirmed COVID-19 patients were included and interviewed. Informed written consent was ensured before participation. Collected data were entered in a predesigned case record form and subsequently analyzed by SPSS-20. Results: Average age of presentation was 37.20±10.02(SD) years with male predominance (77%). Urban presence was in 90%. Thirty-two percent of the patients had comorbidities, with diabetes (16%) and hypertension (19%) being the most frequently observed.The most commonly observed symptoms was fever (65%), followed by cough (58%), breathlessness (42%), Dysgeusia (40%) and fatigue (33%). Mean duration of illness was 8.74±4.8 (SD) days. Overall mortality was 9%. All patients were managed according to the national guidelines and only 7% required ICU support. Conclusion: Patients were mostly middle-aged and male. Typical presentations were fever, cough, breathlessness and dysgeusia. Overall mortality was 9% among the admitted patients and requirement of ICU was 7%. Further study with large sample size is recommended to get a more precise picture. J MEDICINE JUL 2020; 21 (2) : 69-75